Percentage Analysis Mixed of CPO, Phosphic Acid and Sodium Hydroxide as a Replacement for Diesel Engine Oil Fuel Using a Calorize Test (International Journal of Engineering and Computer Science, 2020)
One of the researches being developed is to produce methyl esters from CPO through transesterification reaction of vegetable oil (triglycerides) with methanol. Biodiesel from crude palm oil is a new hope for answering some of the energy needs. know the rate of combustion of the biodiesel produced. Biodiesel that is produced from a mixture of CPO, phosphoric acid and sodium hydroxide, with a percentage of I. 98% CPO, 1% Phosphoric Acid, 1% Sodium Hydroxide: II. 95% CPO, 2% Phosphoric Acid, 3% Sodium Hydroxide: III. 95% CPO, 3% Phosphoric Acid, 2% Sodium Hydroxide. The results showed that the most effective mixture was 95% CPO, 3% acid phosphate and 2% sodium hydroxide with a burning rate of 0.309 g / minute in 30.42 minutes with a final temperature of 57 (oC).